2008
DOI: 10.1074/jbc.m802673200
|View full text |Cite
|
Sign up to set email alerts
|

The Poly(ADP-ribose) Polymerase PARP-1 Is Required for Oxidative Stress-induced TRPM2 Activation in Lymphocytes

Abstract: TRPM2 cation channels are widely expressed in the immune system and are thought to play a role in immune cell responses to oxidative stress. Patch clamp analyses suggest that TRPM2 channel activation can occur through a direct action of oxidants on TRPM2 channels or indirectly through the actions of a related group of adenine nucleotide 2nd messengers. However, the contribution of each gating mechanism to oxidative stressinduced TRPM2 activation in lymphocytes remains undefined. To better understand the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 102 publications
3
103
0
Order By: Relevance
“…Although TRPM2 is activated by ROS and is involved in cell death after oxidative stress (15,16), the activation mechanisms involved are unclear (17)(18)(19)(20). The primary activator of TRPM2 is thought to be ADPR, with most previous studies suggesting that the release of ADPR from the nucleus and mitochondria plays a primary role in TRPM2 activation by H 2 O 2 (17)(18)(19), although one study has reported that H 2 O 2 acts on TRPM2 directly (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although TRPM2 is activated by ROS and is involved in cell death after oxidative stress (15,16), the activation mechanisms involved are unclear (17)(18)(19)(20). The primary activator of TRPM2 is thought to be ADPR, with most previous studies suggesting that the release of ADPR from the nucleus and mitochondria plays a primary role in TRPM2 activation by H 2 O 2 (17)(18)(19), although one study has reported that H 2 O 2 acts on TRPM2 directly (20).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have suggested that TRPM2 activation by H 2 O 2 is caused by ADPR release from intracellular organelles (17)(18)(19). To test this possibility, we evaluated the effects of H 2 O 2 in inside-out single-channel recordings in which intracellular components are absent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21] The male-specific overactivation of PARP-1 in ischemic cell death is particularly relevant because PARP-1-generated adenosine-5 0 -diphosphoribose (ADPr) directly activates TRPM2 channels after exposure to exogenous oxidants. 22,23 Transient receptor potential M2 channels are the only known ion channels to be directly activated by intracellular ADPr, therefore we hypothesize that TRPM2 is a downstream mediator of PARP-1-induced cell death. Several studies report that PARP inhibitors, and deletion of the PARP-1 gene, provides protection in a sexually dimorphic manner, protecting male, but not female, brain.…”
Section: Introductionmentioning
confidence: 93%